2013
DOI: 10.1123/krj.2.3.156
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Kinesiology: Theoretical and Contemporary Considerations

Abstract: In this article, the authors engage in discourse centrally located in the organizational socialization of Black and Hispanic kinesiology faculty and students within institutions of higher education. First, our commentary is situated in the theoretical framework of organizational socialization in regards to insight about the plight of Black and Hispanic kinesiology professionals. Next, data are presented that highlight the status of Black and Hispanic faculty in academe. Informed by previous research, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In 2009, the National Center for Education Statistics reported that only 7% of full-time faculty were African American (Hodge & Corbett, 2013). In 1999, 61% of full-time instructional faculty at HBCUs and 3.8% at PWIs were African American (Betsey, 2008).…”
Section: The Current Climatementioning
confidence: 96%
See 3 more Smart Citations
“…In 2009, the National Center for Education Statistics reported that only 7% of full-time faculty were African American (Hodge & Corbett, 2013). In 1999, 61% of full-time instructional faculty at HBCUs and 3.8% at PWIs were African American (Betsey, 2008).…”
Section: The Current Climatementioning
confidence: 96%
“…All too often, cultural dissonance develops between White and African American faculty at PWIs and, conversely, White faculty at HBCUs experience cultural dissonance, as well (Hodge & Corbett, 2013). Because of this dissonance a conscious effort needs to be made to hear and welcome ideas from new faculty while explaining the hows and whys of a program's current practices.…”
Section: What To Do About This Issuementioning
confidence: 97%
See 2 more Smart Citations
“…Of a more recent note, Kinesiology Review presented a special issue on the matter in 2013. Hodge and Corbett (2013) looked at the experiences of black and Hispanic faculty of color in the United States, and made a similar call for kinesiology to explore the socialization process of Hispanic faculty in the absence of no research studies while calling a more up-to-date study on the experiences of black faculty (Hodge & Stroot, 1997).…”
Section: Confronting "Color-blindness" and Accepting The Need For Racmentioning
confidence: 99%